IMPLEMENTASI APLIKASI SISTEM PENGGAJIAN DENGAN ACTIVITY LOG - Roelly Humdiana, S.Kom., MM., M.Kom (Institut Bisnis dan Informatika Kwik Kian Gie, 2018)
Every company has its own problem that needs to be faced, and every problems should be handled swiftly and flawlessly, so it could compete with other companies. Because of that, the needs of application that helps the company to work efficiently, and tackle every arising problems swiftly and flawlessly is urgent, e.g. Payroll application that works swiftly and accurate. A good payroll system could help the company to maintain its resources efficiently, dan helps maintaining problem that related with worktime managements that could be arise. As for research method that being used for collecting needed data, is done by observation, interviews, and literature studies. The result of this research is payroll application that ease user to maintaining human resources, worktime, and well recorded payroll system. With recorded human resources, worktime, and payroll system in a company, then the company could work more efficiently. Keyword: System, Human Resources, Payroll